Activity of Ethanolic and Supercritical Propolis Extracts in Corynebacterium pseudotuberculosis and Its Associated Biofilm - Santos, Laerte Marlon; Rodrigues, Daniela Méria; Kalil, Maurício Alcantara; Azevedo, Vasco; Meyer, Roberto; Umsza-Guez, Marcelo Andres; Machado, Bruna Aparecida; Seyffert, Nubia; Portela, Ricardo Wagner (Frontiers in Veterinary Science, 2021)
Corynebacterium pseudotuberculosis is the etiological agent of caseous lymphadenitis (CLA) in small ruminants, a chronic disease characterized by the development of granulomas in superficial and visceral lymph nodes, as well as in several organs. An important characteristic of the infection with this bacterium is the formation of biofilm and the absence of effective antibiotic therapy against the disease. From this scenario, the objective of this study was to evaluate the susceptibility of C. pseudotuberculosis to conventional antibiotics and to red, green, and brown propolis extracts obtained by the supercritical and ethanolic extraction methods, as well as its activity in the bacterial biofilm. The results of the sensitivity test using antibiotics indicated a sensitivity of C. pseudotuberculosis strains to the antimicrobial agents. The ethanolic extract of green propolis and the supercritical red propolis extract showed the best antibacterial activities against planktonic C. pseudotuberculosis. A lower antimicrobial activity of the brown propolis extract was identified. Propolis extracts were effective in interfering with the formation of C. pseudotuberculosis biofilm but had little activity on the consolidated biofilm. In conclusion, propolis extracts are more effective against C. pseudotuberculosis in the planktonic stage, being able to interfere with the formation of bacterial biofilm. However, the action of propolis extracts in a sessile and structured microbial biofilm is reduced.